Association of IL10 gene promoter polymorphisms with risks of gastric cancer and atrophic gastritis. Issue 12 (December 2018) - Liu, Sa; Liu, Jing-Wei; Sun, Li-Ping; Gong, Yue-Hua; Xu, Qian; Jing, Jing-Jing; Yuan, Yuan
Objective: To investigate the association between polymorphisms of the interleukin 10 ( IL10 ) gene and risk of gastric cancer (GC) and atrophic gastritis (AG). Methods: This study enrolled patients with GC, patients with AG and healthy control subjects. Demographic data were collected and the IL10 gene –1082A/G, –819C/T and –592A/C polymorphisms were genotyped. An enzyme-linked immunosorbent assay was performed to detect Helicobacter pylori infection. Results: The study enrolled 556 participants including 208 in the GC group, 116 in the AG group and 232 controls (CON group). In a recessive model of the IL10 –819C/T polymorphism, a significantly decreased risk of GC was found compared with AG and non-cancer subjects, respectively (AG→GC: odds ratio OR 0.41; non-cancer→GC: OR 0.57). The CC genotype demonstrated a significantly increased risk of AG compared with CON. Similar significant results were detected in males and H. pylori -negative subgroups. The ACC haplotype was associated with a decreased risk of GC compared with AG. The ATC haplotype was associated with a decreased risk of AG compared with the CON group, but it was associated with an increased risk of GC compared with AG. Conclusion: The IL10 gene promoter –819C/T (rs1800871) polymorphism was associated with the risk of GC and AG in a Chinese population.